KONTRIBUSI KETERAMPILAN MENYIMAK BERITA TERHADAP KETERAMPILAN MENULIS BERITA - Octaviani, Widya; Ratna, Ellya; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACTÂ This article was written to determine at the contribution of news listening skills against the skills of writing mews the student of class VIII SMP Negeri 9 Padang. This research with descriptive methods. The result of this study, there are three points. First, news listening skills is more than enough in qualifying (73,06). Second, news writing skills are in good qualifying (77,88). Third, news listening skills a contribution of 11,40% to the news writing skills the student of class VIII SMP Negeri 9 Padang.Â Kata kunci: kontribusi, menyimak, menulis, berita